The systemic disruption of P2rx7 alleviates tau pathology in P301S tau mice via inhibition of extracellular vesicle release. (20th December 2022) - Abdullah, Mohammad; Ruan, Zhi; Bueser, Katrina Rae; Ikezu, Seiko; Ikezu, Tsuneya
Abstract: Background: P2X purinoceptor 7 (P2RX7), an ATP‐gated cation channel present abundantly in the microglia, induces membrane depolarization and extracellular vesicle (EV) secretion. Previous study demonstrated that administration of GSK1482160, a P2RX7 selective inhibitor, suppressed EVs secretion from murine microglia resulting in accumulation of Tsg101 + intraluminal vesicles (ILVs) in the hippocampus, and restored partial behavioral deficits in P301S tau mice. However, the specificity of GSK1482160 to P2RX7 has never been investigated in P301S tau mice. It is crucial to validate whether P2RX7 is a potential target for alleviating the tauopathy phenotype in P301S tau mice. The purpose of this study is to determine if deletion of P2RX7 is sufficient to recapiturate the therapeutic effect of GSK1482160 in tauopathy mouse model. Method: Fours and nine‐months‐old P2RX7 ‐/‐ :P301S and P301S mice were generated for the evaluation of ILV accumulation and tau pathology. Primary microglia and astrocytes from WT (C57BL/6) and P2RX7 ‐/‐ mice, treated with GSK1482160 and ATP for EV secretion. EVs were isolated from conditioned media via the sequential centrifugation and ultracentrifugation. Finally, EVs were quantified by nanoparticle tracking analysis and exosome specific marker CD9 ELISA. Effects of GSK1482160 on EVs secretion from astrocytes/microglia were also assessed using Western blot with EV specific markers Tsg101 and CD9. Result: Exosome specific marker Tsg101, CD9, and tau expression levels were reduced in the hippocampus of nine‐months‐old P2RX7 ‐/‐ :P301S mice compared to P301S mice. No significant difference between the two groups at 4 months of age was observed. Strikingly, primary cultured microglia and astrocytes showed reduction in EV secretion in both ATP stimulated or unstimulated condition from P2RX7 ‐/‐ group compared to WT group. Additionally, GSK1482160 pretreatment significantly reduced EV secretion from WT astrocytes and microglia, although it had no effects in P2RX7 ‐/‐ cells. These findings were validated by ELISA of EV marker CD9 and immunoblotting of Tsg101 and flotillin‐1 using isolated EVs. Conclusion: Results demonstrate that P2RX7 is primarily responsible for ATP‐induced EV secretion from astrocytes and microglia, and systemic disruption of P2RX7 mimics the effect of GSK1482160 in P301S tau mice, including accumulation of ILVs in microglia and suppression of tau accumulation in the hippocampal regions.